Perceived Burden Due to Registrations for Quality Monitoring and Improvement in Hospitals: A Mixed Methods Study - Marieke Zegers; Gepke L. Veenstra; Gerard Gerritsen; Rutger Verhage; Hans (J.G.); Gera A. Welker (Kerman University of Medical Sciences, 2022)
BackgroundQuality indicators are registered to monitor and improve the quality of care. However, the number and effectiveness of quality indicators is under debate, and may influence the joy in work of physicians and nurses. Empirical data on the nature and consequences of the registration burden are lacking. The aim of this study was to identify and explore healthcare professionals' perceived burden due to quality registrations in hospitals, and the effect of this burden on their joy in work. MethodsA mixed methods observational study, including participative observations, a survey and semi-structured interviews in two academic hospitals and one teaching hospital in the Netherlands. Study participants were 371 healthcare professionals from an intensive care unit (ICU), a haematology department and others involved in the care of elderly patients and patients with prostate or gastrointestinal cancer. ResultsOn average, healthcare professionals spend 52.3 minutes per working day on quality registrations. The average number of quality measures per department is 91, with 1380 underlying variables. Overall, 57% are primarily registered for accountability purposes, 19% for institutional governance and 25% for quality improvement objectives. Only 36% were perceived as useful for improving quality in everyday practice. Eight types of registration burden were identified, such as an excessive number of quality registrations, and the lack of usefulness for improving quality and inefficiencies in the registration process. The time healthcare professionals spent on quality registrations was not correlated with any measure of joy in work. Perceived unreasonable registrations were negatively associated with healthcare professionals' joy in work (intrinsic motivation and autonomy). Healthcare professionals experienced quality registrations as diverting time from patient care and from actually improving quality. ConclusionRegistering fewer quality indicators, but more of what really matters to healthcare professionals, is key to increasing the effectiveness of registrations for quality improvement and governance. Also the efficiency of quality registrations should be increased through staffing and information and communications technology solutions to reduce the registration burden experienced by nurses and physicians.